AI EPISTEMOLOGY IN ISLAMIC PERSPECTIVE: A BIBLIOMETRIC ANALYSIS - Susanti, Lia; Robandi, Babang; Suhadha, Abdul Karim; Najmudin, Dudun; Rahman, Gunawan Anggia (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research explores the epistemology of artificial intelligence (AI) from an Islamic perspective to fill the gap in the literature that mostly only discusses the technical and ethical aspects of universal AI. Using bibliometric methods, this study analyzes trends, collaborations between researchers, and major themes in AI-Islamic studies, based on 200 documents from Google Scholar for the period 2015-2024. The analysis includes keyword co-occurrence, co-authorship, and citation density, with network map visualization through VOSviewer. The results show that AI is increasingly being applied in the fields of education, Islamic finance, and social management in Muslim societies, along with the increasing adoption of this technology globally. However, there are significant challenges related to the ethical, fair, and relevant application of AI to Islamic values, including the integration of Shariah principles in technology development. This research highlights opportunities to utilize AI to support the values of justice, welfare, and environmental stewardship grounded in Islamic spirituality. It contributes to the literature by integrating Islamic ontology, ethics, and epistemology in AI development, providing guidance that is not only conceptual but also applicable. It also highlights the need for cross-disciplinary collaboration to address emerging ethical and social challenges. As such, this research is not only relevant for Muslim societies but also offers a global perspective on how modern technology can be directed to support broader humanitarian goals based on Islamic values.